PERSEPSI DAN RESPON WANITA TERHADAP PERKEMBANGAN PELACURAN DI KOTA DENPASAR - Eka Martiningsih, Ni Gst. Ag. Gde (Jurnal Studi Jender SRIKANDI; Vol. 6, No. 1 Januari 2007, 2012)
The prostitution constitute threat toward sex morality, households life, health, female welfare, and become problem for local government. However, prostitution always exist, and very difficult to destroy. Similarly, in Denpasar City the problem of prostitution never finish.The objective of this research was to evaluate (1) perception and response of female toward prostitution development in Denpasar City, (2) some factors that correlated to perception and response female toward prostitution development in Denpasar City.To determine of sample used purposive sampling method, with the amount of sample 150 persons. Perception and response of female toward prostitution analyzed in descriptive, while to evaluate some factors that correlated to perception and response of female toward prostitution analyzed by Chi-Square.The result of this research indicated that (1) perception and response of female toward prostitution development were negative category, (2) factors that correlated to perception and response of female toward prostitution were factor of economic and psychological .
Keywords: Perception, Response, Prostitution